Relations between the Kurdistan Republic and the Government of Azerbaijan - مستەفا, ئارام عەلی; محەمەد, ڕێواس فەتاح (Sulaimani Journal for Humanities, 2019)
The Kurdish and Azari National Movements in the wake of the Second World War and the occupation of Iran by the Anglo-Soviet forces, which formed the parties of the Democratic Azerbaijani Party and the Kurdistan Democratic Party- Iran. These two parties formed a government in areas under their control. The two governments signed a treaty of cooperation between the two republics, and have worked to exchange views and put differences aside according to the common interests of the two republics, which are starting from the Rezaia and its environs, such as Salamas, Khoi, Maku, Miandwaw, Tikab and others. Despite the Treaty of Friendship between the two republics of 23 April 1946 and the recognition of the independence of the Republic of Kurdistan by the Republic of Azerbaijan, this agreement was granted no political recognition by the Kurdish public, as it was not granted international legal recognition. Thus, the interests of the Kurdistan Republic went to the interests of the Republic of Azerbaijan, where the Kurdish issue was pushed aside, because of the agreement signed on 13 June 1946 between Tehran and Tabriz without the presence or participation of the kurds in the negotiations.